Effect of ischaemia on sensory potentials of normal subjects of different ages. Issue 3 (June 1973) - Caruso, Giuseppe; Labianca, Orazio; Ferrannini, Ermanno
Abstract : In 73 normal subjects, from 10 to 82 years of age, maximum orthodromic sensory nerve conduction velocity was measured in the median nerve before and during a 30 minute period of vascular occlusion. During ischaemia progressive slowing in conduction velocity, decrease in amplitude, and increase in duration of the sensory action potential evoked at wrist and elbow by supramaximal stimulation of digit III were observed. However, a statistically significant difference (P<0·05 to P<0·01) between subjects was noted by grouping them by age: the older the subject, the longer the persistence of sensory response and the less marked the slowing in conduction velocity. The mechanism of the phenomenon has been discussed in relation to a similar longer resistance to ischaemia found in peripheral nerves of diabetic and uraemic patients.